BIODIVERSITY OF INVERTEBRATES OF PUERTO VIEJO WETLAND, LIMA, PERU - Iannacone, Jose (2007)
Puerto Viejo is a coastal wetland of importance for resident and migratory birds conformed by several seasonal, natural and artificial water bodies with high salinities. This ecosystem is located to the south of Lima, Peru. In June of the 2004 surveys of the biodiversity and abundance of the invertebrate community were carried out, representing a spatial heterogeneity of different littoral water bodies in 28 stations of sampling distributed in five lagoons dispersed in all marsh area. Distribution of stations by lagoon were: lagoon 1 (n=2): stations 1 and 2; lagoon 2 (n=5): stations 3 to 7; lagoon 3 (n=6): stations 8 to 13; lagoon 4 (n=9): stations 14 to 22, and finally lagoon 5 (n=6): stations 23 to 28. The samples of zooplankton were collected using a plankton net of 75 of diameter and preserved using a solution of formalin sweetened to 4 %. In addition, some limnological parameters like conductivity (Ohms•cm-2), coefficient of extinction, temperature of the water (°C) and temperature of the air (°C) in each station of sampling were determined. The results indicated the presence of 40 taxa, being more abundant and frequent; the rotifers Brachionus calyciflorus (Pallas, 1776) and Lecane lunaris (Ehrenberg, 1831), the nematode Rhabdolaimus sp. Man, 1980, the copepod Cyclops strennus (Fisher, 1851), insect Chironomini and the foraminifer Globoratalia scitula Brady, 1877. The number of organisms by liter (N° org. L-1) was of 14 (4-45) and the number of taxa by sampling station was of 10 (5-20). The diversity index mean of Shannon-Wiener was relatively high. Similarity indexes showed values higher than 30% of similarity between 28 stations of sampling. It concluded that 37 of 40 taxa are new records for Puerto Viejo wetland, Lima, Peru.